A deep learning-based edge-fog-cloud framework for driving behavior management. (December 2021) - Al-Rakhami, Mabrook S.; Gumaei, Abdu; Hassan, Mohammad Mehedi; Alamri, Atif; Alhussein, Musaed; Razzaque, Md. Abdur; Fortino, Giancarlo
Highlights: A deep learning-based cognitive framework is proposed on edge-fog-cloud platform. The framework is used for real-time detection and monitoring of driving behaviors. Training/retraining the deep learning models in small devices face several challenges. Proposed a lightweight and computationally efficient deep neural network. Reduced the communication overheads by performing the task on fog computing. Abstract: Among the various reasons behind vehicle accidents, drivers' aggressiveness and distractions play a significant role. Deep learning (DL) algorithms inside a car mobile edge (CME) have been used for driver monitoring and to perform automated decision-making processes. Training and retraining the DL models in resource-constrained CME devices come with several challenges, especially regarding computational and memory space costs. Moreover, training the DL models periodically on representative data nearest to CME without imposing communication overheads on the cloud improves the quality of service (QoS) parameters, such as memory demand, processing time, power consumption, and bandwidth. This paper investigates the deployment of a deep neural network (DNN) model on a cloud-fog-edge computing framework for aggressive driver behavior detection and monitoring. To reach this goal, our framework proposes utilizing effective systems and databases of sensor-based metrics and data, cost-effective wireless networks, cloud-and fog-edge computing technologies, and the Internet. Experimental results of the DNN model showed that the accuracy of detection is improved by 1.84% compared with the current related work without any pre-processing window on data points that come from bio-signal sensors. Moreover, the experimental results of the networking part prove the efficiency and effectiveness of the proposed framework. Graphical abstract: Edge-Fog-Cloud Framework for Driving Behavior Detection and Monitoring. Image, graphical abstract